Pengaruh spiritualitas terhadap kepatuhan dan kualitas hidup pasien orang dengan human immunodeficiency virus (ODHIV): A systematic review - Erien, Fajar; Nursalam, Nursalam (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Treatment adherence and quality of life in patients living with HIV (PLHIV) remain serious issues. Patient spirituality may be a solution because it can provide peace of mind and have a positive psychological impact. Purpose: To analyze the influence of spirituality on treatment availability and quality of life in patients living with human immunodeficiency virus (PLHIV). Method: A systematic review and selection of articles based on the eligibility criteria of Population, Intervention, Comparator, Outcome (PICO) were obtained from three major databases: PubMed, Scopus, and Proquest. Keywords used included